A Metallic Room‐Temperature Oxide Ion Conductor1. Issue 28 (27th May 2014) - Heise, Martin; Rasche, Bertold; Isaeva, Anna; Baranov, Alexey I.; Ruck, Michael; Schäfer, Konrad; Pöttgen, Rainer; Eufinger, Jens‐Peter; Janek, Jürgen
Abstract Nanoparticles of Bi3Ir, obtained from a microwave‐assisted polyol process, activate molecular oxygen from air at room temperature and reversibly intercalate it as oxide ions. The closely related structures of Bi3Ir and Bi3IrOx (x≤2) were investigated by X‐ray diffraction, electron microscopy, and quantum‐chemical modeling. In the topochemically formed metallic suboxide, the intermetallic building units are fully preserved. Time‐ and temperature‐dependent monitoring of the oxygen uptake in an oxygen‐filled chamber shows that the activation energy for oxide diffusion (84 meV) is one order of magnitude smaller than that in any known material. Bi3IrOx is the first metallic oxide ion conductor and also the first that operates at room temperature.